O Interjecto - Adalberto Müller (O Que Nos Faz Pensar)
At the height of the late Modernity crises, the subject/object dichotomic paradigm has been called into question on various philosophical and cultural fronts. In this context, we propose the concept of interject and interjective relations to think of the gap or border where the conjunctions and disjunctions of experience take place.